Single-center experience with a unibody single-branched stent graft for zone 2 thoracic endovascular aortic repair - Kong, Xiang; Ruan, Peng; Yu, Jiquan; Chu, Tianshu; Gao, Lei; Jiang, Hui; Ge, Jianjun (Frontiers in Cardiovascular Medicine, 2022)
To provide an adequate proximal landing zone, left subclavian artery (LSA) reconstruction has become an important part of thoracic endovascular aortic repair (TEVAR). This study evaluates the short and medium term efficacy of a novel unibody single-branched stent graft for zone 2 TEVAR. Fifty-two patients (mean age, 56 ± 10.9 years; 42 men) with distal aortic arch lesions requiring LSA reconstruction received unibody single-branched stents from September 2019 to March 2021. Computed tomography angiography was performed 6, 12, and 24 months after surgery to observe stent morphology, branch patency, endoleaks, stent-related adverse events, and changes in the diameter of true and false lumens. All stents were deployed adequately, and the technical success rate was 100%. The mean operation time was 121.8 ± 47.0 min. The mean postoperative hospital stay was 6.2 ± 3.7 days, and the mean follow-up was 16.8 ± 5.2 months (range, 12–24 months). During follow-up, there were no deaths and complications such as stent displacement or fracture, stenosis, fracture, occlusion, and type Ia endoleaks. The patency rate of the branched segment was 100%. In 42 patients with aortic dissection (AD), the true lumen diameter of the aortic isthmus was 29.4 ± 2.9 mm after surgery, significantly larger than before surgery (20.6 ± 5.4 mm, P < 0.05). Postoperative aortic isthmus false lumen diameter was significantly smaller than that before operation (6.1 ± 5.2 mm vs. 16.0 ± 7.6 mm, P < 0.05). The new unibody single-branched stent for zone 2 TEVAR is safe and accurate, and its efficacy is good in the short and medium term.